2017
DOI: 10.1007/s10519-017-9834-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Associated with Honey Bee Grooming Behavior in Response to Varroa Mites

Abstract: Honey bee (Apis mellifera) grooming behavior is an important mechanism of resistance against the parasitic mite Varroa destructor. This research was conducted to study associations between grooming behavior and the expression of selected immune, neural, detoxification, developmental and health-related genes. Individual bees tested in a laboratory assay for various levels of grooming behavior in response to V. destructor were also analyzed for gene expression. Intense groomers (IG) were most efficient in that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 57 publications
(81 reference statements)
0
43
2
4
Order By: Relevance
“…In their study in drosophila, they reported that DopR gene, acting in neural and hormonal regulation, was effective in grooming behavior. And other studies also have found a relationship between grooming behavior and expression of neural genes (Arechavaleta-Velasco et al, 2012;Tsuruda et al, 2014;Najavas et al, 2008;Hamiduzzaman et al, 2017;Mustard et al, 2010). In gene expression studies in honey bees, expression of neural genes was found to be directly proportional to the behavior of grooming.…”
Section: Resultsmentioning
confidence: 88%
“…In their study in drosophila, they reported that DopR gene, acting in neural and hormonal regulation, was effective in grooming behavior. And other studies also have found a relationship between grooming behavior and expression of neural genes (Arechavaleta-Velasco et al, 2012;Tsuruda et al, 2014;Najavas et al, 2008;Hamiduzzaman et al, 2017;Mustard et al, 2010). In gene expression studies in honey bees, expression of neural genes was found to be directly proportional to the behavior of grooming.…”
Section: Resultsmentioning
confidence: 88%
“…In humans it binds alpha neurexins, a group of presynaptic transmembrane receptors that promote adhesion between dendrites and axons [52]. Neurexins have been linked to behavioural response to parasites in bees [53] and in host response to parasite infection in hard clam, Mercenaria mercenaria [54]. While not an obvious functional candidate, NXPE3 is worthy of further investigation in host resistance to sea lice due to its differential expression and overlap with a genomic region showing putative differentiation between resistant and susceptible fish.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour has also been identified in naturally surviving A. mellifera populations such as Tunisian A. m. intermissa (Boecking and Ritter, 1993;Ritter et al, 1990) and Africanised honey bees in Mexico (Arechavaleta-Velasco and Guzman-Novoa, 2001;Mondragon et al, 2005). Laboratory experiments have been conducted (Hamiduzzaman et al, 2017;Hoffmann, 1996;Invernizzi et al, 2016;Kirrane et al, 2012;Szabo et al, 1996;Thakur et al, 1997) and encouraged the implementation of grooming as a field trait (Table SF).…”
Section: Trait Reducing V Destructor Infestation On Adults: Groomingmentioning
confidence: 92%
“…This widespread monitoring may help to identify numerous loci with a direct impact on the resistance of colonies of western honey bee against the Varroa mite. Many loci linked to diverse resistance traits have already been identified (Arechavaleta-Velasco et al, 2012;Behrens et al, 2011;Broeckx et al, 2019;Guarna et al, 2017;Hamiduzzaman et al, 2017;Harpur et al, 2019;Hu et al, 2016;Jiang et al, 2016;Lapidge et al, 2002;Morfin et al, 2019a;Oxley et al, 2010;Spötter et al, 2016;Spötter et al, 2012;Tsuruda et al, 2012;Zakar et al, 2014). Even though each of these studies mentions the possibility of using marker-assisted or genomic selection in honey bee breeding, to the best of our knowledge, the identified sequences have not been routinely implemented in selection programmes.…”
Section: Integrating Genomic Datamentioning
confidence: 99%